2012
DOI: 10.4149/bll_2012_095
|View full text |Cite
|
Sign up to set email alerts
|

Major and minor bio-element status in children with febrile seizure

Abstract: Febrile seizures (FS) are the most common cause of seizures in children. The exact etiopathogenesis is unknown but involves factors like genetic predisposition and alterations in the levels of neurotransmitters and some trace elements. The study includes 48 consecutive children with FS, and 55 healthy age matched control subjects. Calcium, magnesium and potassium concentrations in the febrile study group were lower than in the control group (p<0.05). Iron and Gallium levels in the study group were lower than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
2
14
1
2
Order By: Relevance
“…Regarding serum iron the mean level was 39.21±23.53 ;( 11-110) μg/dL in group A and 113.47 ±35.0;( 57-176) μg/dL in group B as P value was (<0.001), and there was high significant statistical difference between anemic group A and anemic group B as mean Serum iron was 31.63±16.83;( 11-70.5) μg/dL in anemic group A and was 107.73±11-70.5;( 57-167) μg/dL in anemic Group B. This agrees with the study of Akbayram et al , who indicated that in children with febrile convulsions, serum iron levels were lower than those in the control febrile group but without febrile convulsions [7]. Also, Gencer et al, found a statistically significant difference (p=0.03) between the cases and control group at mean serum iron level [8].…”
Section: Discussion:-supporting
confidence: 82%
See 2 more Smart Citations
“…Regarding serum iron the mean level was 39.21±23.53 ;( 11-110) μg/dL in group A and 113.47 ±35.0;( 57-176) μg/dL in group B as P value was (<0.001), and there was high significant statistical difference between anemic group A and anemic group B as mean Serum iron was 31.63±16.83;( 11-70.5) μg/dL in anemic group A and was 107.73±11-70.5;( 57-167) μg/dL in anemic Group B. This agrees with the study of Akbayram et al , who indicated that in children with febrile convulsions, serum iron levels were lower than those in the control febrile group but without febrile convulsions [7]. Also, Gencer et al, found a statistically significant difference (p=0.03) between the cases and control group at mean serum iron level [8].…”
Section: Discussion:-supporting
confidence: 82%
“…Reference ranges for serum iron were 40-100 μg/dl for infants and 50-120 μg/dl for children. For TIBC, reference ranges were 100-140 μg/dl for infants and 250-400 μg/dl for children [6].Serum ferritin was detected using Biosystem BTS-350: (Spectrum Diagnostic Ferritin Turbi Latex).Transferrin saturation was calculated using the following formula: transferrin saturation = iron level/TIBC×100 (normal value = 20-45%) for [7] C-reactive protein more than 6 mg/dl was considered positive. In group A, Considering the fact that infection can affect iron panel studies by increasing serum ferritin level (usually by more than 50 μg/l if no iron deficiency) and decreasing serum iron level and TIBC.…”
Section: Methods:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Akbayrams et al 36 in a study, where 48 children with febrile seizures were compared with age matched controls found low serum calcium (P<0.05) and iron (P=0.001), where it was aimed to find if any change in element levels occur in children with febrile seizures. In present study only 4% of cases had both iron deficiency anemia and febrile convulsions.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Akbayramset al [13] where 48 children with febrile seizures were compared with age matched …”
Section: Discussionmentioning
confidence: 99%